If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + 2w = -6 Solving -10 + 2w = -6 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 2w = -6 + 10 Combine like terms: -10 + 10 = 0 0 + 2w = -6 + 10 2w = -6 + 10 Combine like terms: -6 + 10 = 4 2w = 4 Divide each side by '2'. w = 2 Simplifying w = 2
| -11y+5y=14 | | 6/y=3/7 | | 3+77x=44x+6 | | 32-15x=-18+9 | | 11/10=y/12 | | 4k+33=1-3k | | 8g-5w=4 | | a/10=4/9 | | 4a^9+5=8 | | 7+5y-4=6y+6-2y | | 3*(3-x)=5x+27 | | 7x-42=2x+12 | | 4x+10=-35-5 | | 1j^5-7=12 | | X-10=-4X | | 5b^2-36b=32 | | a+f=10 | | 1k+q=8 | | 3+10x=-6+x | | 2x-4=5x-12 | | 47x+(-13y)=0 | | 2t+2s=3b | | 36=96%.x | | 36=96%xX | | y=-8x+400 | | 2530=15 | | 7(7-3)=-u+11 | | 36=96%*x | | 404=27x+80 | | -.5(2y+5)=0.5(-7-4y) | | 5x+2=33 | | 9z+5=3 |